Attributes of highland ecotourism in Northern Peninsular Malaysia: a case study of resident knowledge - Jabil Mapjabil,; Chan, Ngai Weng; Norizan Md Nor,; Suriati Ghazali,; Badariah Ab Rahman,; Rosmiza Mohd Zainol,; Mazdi Marzuki, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Ecotourism is one of the tourism sectors that is becoming popular and has attracted scholars in various fields of studies. This paper highlights residents’ perceived knowledge of the ecotourism concept and its particular attributes in the highlands of northern Peninsular Malaysia. The case study was conducted in Gunung Jerai, Gunung Mat Chincang, Kedah, Penang Hill, Penang and Maxwell Hill, Perak involving field surveys of 462 randomly sampled respondents. The residents’ knowledge levels of the definition of ‘ecotourism’ in the study areas were found to be relatively low ( below 50%). Demographically, the majority of the respondents were males, below 30 years old with secondary educational background and had been residents for more than 20 years. With respect to dense forests, highlands, falls and rapids as major highland ecotourism destinations in Peninsular Malaysia the majority of the respondents chose recreation and the picturesque scenery as the main attributes of highlands ecotourism. Other highland attributes of cultural diversity, poverty and difficulty of access were not perceived as attributes representing the place identity of the study areas. Instead, planning problems, development control, promotion and environmental deterioration were identified as issues and challenges encountering the development of all northern Peninsular Malaysia ecotourism areas studied. Thus, efforts to enhance the level of knowledge and awareness of highland ecotourism have to be given due attention. All stakeholders including local residents should be more committed and involved in the process.